Influence of roller - burnishing on surface roughness parameters and roundness - Görög Augustín; Görögová Ingrid; Stančeková Dana; Janota Miroslav (MATEC Web of Conferences, 2018)
In order to increase productivity, machining times and market competitiveness of machining production systems, it is important to continuously develop existing technological solutions. The paper deals with surface roughness and roundness after roller burnishing outer rotary surface. Roller burnishing was applied on turned surfaces with different surface roughness. Each outer rotary surface was roller burnished twice with the same conditions (pressing force, peripheral speed of machine part, feed of tool). The parameters of the surface roughness Ra, Rq and Rt were measured after each single roller burnishing. The results show that the surface roughness is decreasing after the first roller burnishing cycle (additional roller burnishing had only negligible influence on surface roughness) and the original surface roughness has a significant influence on change of surface roughness after roller burnishing.